The diagnosis of mycobacterial infection in HIV-positive individuals (Colombia Medica, 1994)
Infection with Mycobacterium tuberculosis has been reported as a common complication of human immunodeficiency virus infection among groups with a high prevalence of tuberculosis (TBC). The frequency of colonization and disease attributable to mycobacteria other than tuberculosis (MOTI) has increased, too. Methods for diagnosis of TBC and MOTI and the general clinical features of mycobacterial infections were assessed in 155 HlV-infected patients from the Social Security Institute (ISS). A high prevalence of TBC (6.5%) was observed, and atypical clinical presentation with extrapulmonary involvement was common. MOTI was isolated in 43 (27.7%) individuals, in 9 out of the 43 patients were associated with human disease. The most frequent MOTI found were the M. avium complex and M fortuitum (4.5%). For this reason, proper facilities for early diagnosis of mycobacterial diseases, particularly TBC, are critical in mv-infected patients. The awareness of physicians combined with exhaustive research through sensitive laboratory methods in HIV-infected patients will be of great importance in our conditions for the improvement of life quality among JilV-infected people.